Prevalence and antibiogram of Salmonella species isolated from poultry products in Ebonyi State, Nigeria - Ifeanyichukwu, Iroha; Chika, Ejikeugwu; Ogonna, Anioketta; Chidinma, Iroha; Monique, Ajah; Ikechukwu, Moses; Stanley, Eluu; Emmanuel, Nwakaeze; Ngozi, Afiukwa; Agabus, Nwuzo (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study evaluated the occurrence and antimicrobial susceptibility profile of Salmonella species isolated from various poultry products including chicken meat, poultry eggs, poultry birds drinking water, and poultry feed. Materials and methods: A total of 79 samples comprising of chicken meat (n=20), egg shell (n=15), poultry egg contents (n=18), drinking water (n=14), and poultry feed (n=12) were bacteriologically and microscopically analyzed for the isolation of Salmonella species. Results: Overall, this study reported a high prevalence of Salmonella species (62%) from various poultry products especially in poultry (chicken) meat and poultry egg contents where the percentage occurrence of Salmonella species was 100% and 20.4% respectively. The antibiogram conducted on the Salmonella species isolated from the various poultry samples reveal that all the isolates were multi-drug resistant to more than 50% of the tested antibiotics especially to tetracycline, gentamicin, tobramycin, nitrofurantoin and imipenem. However, most of the Salmonella species were also found to be highly susceptible to ceftriaxone, cefotaxime, ertapenem and ceftazidime. It was also observed in this study that the highest level of resistance to the tested antibiotics was recorded in Salmonella species isolated from poultry meat samples. Conclusion: Salmonellosis due to the consumption of contaminated or infected poultry products could pose serious public health problem to the general public if allowed. Thus, poultry farms and other poultry product outlets should be operated under sanitized conditions that ward-off the incidence of foodborne pathogens such as Salmonella. The use of antibiotics as growth promoting agents and prophylaxis in the production of poultry birds in this region should be discouraged since such practices allowed drug-resistant bacteria to emerge and spread in the community. http://doi.org/10.5455/javar.2016.c-172